The First Sense: A Philosophical Study of the Sense of Touch: Exploring touch: A review of Matthew Fulkerson's The First Sense. (2nd January 2016) - Batty, Clare
Abstract : In this essay, I review Matthew Fulkerson's The First Sense: A Philosophical Study of the Sense of Touch . In this first philosophical book on the sense of touch, Fulkerson provides an account of the nature and content of tactual experience. Central to Fulkerson's view is the claim that exploratory action plays a fundamental role in touch. In this review, I put pressure on two of his arguments: (1) the argument that tactual experience is unisensory and (2) the argument that tactual experience does not depend on explicit bodily awareness.